Comparative analysis of level of service (LOS) under varying lighting conditions [electronic resource] - Seyed Hossein Hosseini, 1972-; Fakulti Kejuruteraan Awam (2011)
Thesis (Sarjana Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2011